1988
DOI: 10.1152/jappl.1988.64.5.1810
|View full text |Cite
|
Sign up to set email alerts
|

Increased resting energy expenditure in cystic fibrosis

Abstract: To explore the hypothesis that there is an increased metabolic rate in cystic fibrosis, resting energy expenditure was measured by indirect calorimetry in 23 subjects with cystic fibrosis in a stable clinical state and in 42 normal control subjects. Resting energy expenditure was found to be elevated by an average of 0.45 MJ/24 h [95% confidence interval (CI) = 0.26-0.64, t = 4.91, P less than 0.001] (108 kcal/24 h), or 9.2% above expected values derived from the regression relating resting energy expenditure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0
4

Year Published

1991
1991
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 0 publications
6
44
0
4
Order By: Relevance
“…It has been con®rmed that REE is elevated in patients which is consistent with previous research (Vaisman et al, 1987a,b;Buchdahl et al, 1988;O'Rawe et al, 1992;Grunow et al, 1993;Horswill et al, 1994;Bell et al, 1995Bell et al, , 1999Stallings et al, 1998). There were also signi®cant increases in the ECA in patients with CF during walking, even when the contribution of REE was accounted for.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It has been con®rmed that REE is elevated in patients which is consistent with previous research (Vaisman et al, 1987a,b;Buchdahl et al, 1988;O'Rawe et al, 1992;Grunow et al, 1993;Horswill et al, 1994;Bell et al, 1995Bell et al, , 1999Stallings et al, 1998). There were also signi®cant increases in the ECA in patients with CF during walking, even when the contribution of REE was accounted for.…”
Section: Discussionsupporting
confidence: 89%
“…There was no relationship between REE and genotype, which is consistent with others (Fried et al, 1991;Tomezsko et al, 1994). Researchers have also suggested that the increase in REE is related to pulmonary function (Vaisman et al, 1987a,b;Buchdahl et al, 1988;Fried et al, 1991;Amin & Dozor, 1994), however this study did not ®nd any relationship between REE and FEV 1 or FVC. This may be due to the small sample size or the small range in pulmonary function scores observed in this study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations